A review on soil radionuclide distribution in Iraq analysed using gamma ray spectroscopy. Issue 1 (3rd April 2021) - Ahmed, Rasha S.
Abstract: Human being exposed to naturally occurring ionizing radiation throughout their lives as these radionuclides are present in different amounts in our environment. Gamma radiation emitted from uranium (U), thorium (Th), radium (Ra), potassium (K) and cesium (Cs) radionuclides and their decay products represents the essential external source of radiation to human beings. The amount of these radioactive elements differs from one region to another. These radioactive nuclides may enter into the human body through air inhalation or by eating and drinking. When the concentration of these radioactive elements reaches hazardous limits, it may cause cancer like lung, stomach and blood cancers. For purposes of monitoring the health hazards caused by the ionizing radiation, radionuclide activity concentrations are being measured in soil, sand, water, rocks, air etc. In Iraq and different regions around the world pollution of soil is a major concern with respect to its contaminant, existing in the food chain and persistence in the environment. In this work, several data have been reported and reviewed from a number of studies that measure 238 U, 226 Ra, 232 Th, 137 Cs and 40 K radionuclides activity in the soil of Iraq, specifically in Salahadeen, Bsrah, Erbil, Sulaimanya, Najaf, Nineveh, Kirkuk, Babylon, Thi-Qar, Al Anbar, Al-Muthanna, Karbala and Hilla governorates. In all articles, NaI (Tl) and high-purity germanium (HPGe) detectors are used for radioactivity measurements. From this review, it can be deduced that the average activity concentrations for the measured radionuclides in soil were below worldwide average levels established by UNSCEAR except in Sulaimany, Basrah and Baghdad where elevated levels of 238 U, 226 Ra and 40 K were noticed. Additionally, 137 Cs has been recorded in some Iraqi regions.